Perceived turnover intention model of academic in selected private universities in Malaysia - Ramasamy, Vijayan (2020)
Quality of the academics is one of the most important components in higher education’s quality assurance. Turnover among academic, however, could undermine the efficiency, productivity and to a certain extent, threaten the institution’s long-term survival. Preliminary interviews with human resource personnel of selected private higher institutions revealed high academic turnover rate of 18%. This research attempts to explore the reason for turnover intention among academic in selected private higher education in Malaysia. Although much has been done to investigate the various reasons for turnover, little is known at this selected private higher education institutions. This research utilized a mixed method approach. In the qualitative phase, in-depth interviews were conducted with resigned academic from selected private higher education institutions. The NVivo 8 software was used to analyze the data thematically. Seven major themes emerged from this analysis. Although the majority of factors could be traced to previous literature there are two emerging themes which are employer brand and cyberbullying that warrants further scrutiny. In the quantitative phase, an exploratory survey was conducted to examine the influence of cyberbullying, employer brand, perceived job alternative, work overload, job insecurity, perceived procedural justice and distributive justice on turnover intention. Stratified random sample technique was used to select respondents from selected private universities. Structural Equation Modeling (SEM) using Smart PLS software version 3 was used to test the hypothesis. Findings revealed that employer brand, perceived alternative job, job insecurity and work overload significantly influence turnover intention among academics. This study contributes to the robustness of Unfolding Model of Turnover, associating these constructs and turnover intention. Moreover, the findings are also significant as it contributes very much to the theory, practice and methodology of future research. The practical application has weight about a new perspective in managing turnover issue among private higher education institutions. This research shed some light on the management of private higher education institutions, especially in strategizing on how to minimize the high turnover rates. An emerging finding of employer brand provides some initial insight of its role in turnover literature and warrants further security in future studies.